Pemberdayaan Masyarakat Melalui Pengelolaan Limbah Pertanian Berbasis Zerowaste dalam Menunjang Pengembangan Edutourism Subak Perkotaan - L P K Pratiwi; N Yudiarini; N N A Suryandari (Cakrawala: Jurnal Pengabdian Masyarakat Global, 2023)
Subak Padanggalak is one of the agricultural areas of Denpasar City which was developed as educational tourism to support the sustainability of urban agriculture. The problems faced by partner groups include: there is no management of agricultural waste, they have not implemented organic-based farming, and they have not managed educational tour packages optimally. The aim of the program is community empowerment through zero-waste-based agricultural waste management in supporting the development of urban Subak edutourism. The PKM method uses knowledge transfer based on a participatory action program. The research results showed that before the training, knowledge of integrated waste management into organic products applied increased from 27.50% less interested to 62.50 to very interested. Meanwhile, participants' interest in applying and selling the product was from 63.00% quite interested, increasing to 74.50% of people saying they were very interested. With this training program, it is hoped that we can streamline production costs, optimize the packaging of educational tour packages to increase income, and preserve the environment.